(untitled) (Journal of the College of Basic Education, 2023)
Most of the critical discourse analysis is directed to analysing media discourses and political discourses, however; literary works can be subjected to critical discourse analysis on different levels such as drama and novels. This paper focuses on employing Critical Discourse Analysis (CDA) in investigating linguistic and rhetorical devices of Hemingway’s The Old Man and the Sea. The main objective of the current study is to analyse the literary texts selected from The Old Man and the Sea in terms of linguistics and rhetorical features by adopting two models: Fairclough’s three-dimensional model (2001) and Burke’s four master tropes model (1969). The study has reached the following concluding points: Hemingway uses more informal and simple vocabulary and concrete specific words. Besides, the linguistic analysis shows that the present discourse uses conjunctions and pronouns, and the current social analysis has different occasions including Santiago, the boy, and the fish.